The effect of reaction temperature on structural and morphological properties of Mn2O3 nanoparticles and its application of electrochemical and gas sensor. (6th December 2022) - Rajyashree, L.; Manoharan, C.; Loganathan, A.; Venkateshwarlu, M.; SanjayKumar Arasumani,
ABSTRACT: Manganese oxide nanoparticles (Mn2 O3 NPs) is a potential material for various applications. In this work, Mn2 O3 NPs were synthesised by hydrothermal method for their superior performance in ammonia (NH3 ) gas sensor application. XRD analysis revealed a cubic structure with the space group (Ia3) and the average crystallite size varied from 52 to 86 nm, which had consistent with the transmission electron microscopy (TEM) image. Scanning electron microscopy (SEM) analysis showed that calcination temperature played a significant role in the morphological changes in NPs, which obviously converted them rod like to spherical structures. BET measurement exhibited the surface area of 24.6 m 2 /g.   The electrochemical performance of Mn2 O3 electrode was accomplished to pseudocapacitive nature and had better specific capacitance of 386 F/g at 10 Vs −1 with good electrocatalytic activity. For gas-sensing applications, Mn2 O3 NPs exhibited better selectivity towards ammonia in the presence of other gases. The response and recovery time towards NH3 were found to be 60s and 62s, respectively.